The Interactive LMS Application Based on the Litera-Tech Model to Enhance Students' Understanding of Basic Literacy Instruction in Elementary Schools - Supartinah, Supartinah; Firdaus, Fery Muhamad; Sugiarsih, Septia; Sayekti, Octavian Muning (UIN Sunan Kalijaga Yogyakarta, 2025)
LMS emerged as a response to the development of information technology and the need to simplify and improve education management. Digital technology in learning refers to using digital tools and systems that facilitate a more interactive and dynamic learning process. The development model used in this study is the ADDIE model The Undergraduate Program in Elementary School Teacher Education (PGSD), Faculty of Education, Yogyakarta State University (FIP UNY), was the subject of this research. The determination of research subjects was carried out purposively. The product trials in this study were conducted in two stages: the main trial, involving 50 trial subjects from undergraduate PGSD students at FIP UNY, and the operational field trial, also involving 100 trial subjects from undergraduate PGSD students at FIP UNY. The developed product underwent validation by subject matter experts and design experts. The obtained data were processed using descriptive percentage techniques and then converted into quantitative descriptive data.. The results of the design expert validation of nine aspects of the interface, user media, navigation, interactivity, feedback, affective considerations, robustness, invisible features, and help and support showed an average score of 3.87 within the range of 3.41 - 4.00, which, according to the assessment criteria, is included in the